The Effect of Saccharin on SnNi Alloy: the Electrodeposition and its Electrocatalytic Activity in Ethanol Oxidation Reaction - Mulmeyda, Rinda; Abdul Ghofur Sidik; Chika Shafa Maura; Abdul Asywalul Fazri (Pusat Inovasi Sains, 2024)
The development of Direct Ethanol Fuel Cell (DEFC) has attracted much attention, as alternative energy sources due to its various advantages. However, among its various advantages, DEFC has several problems, such as the kinetics of the ethanol oxidation reaction. Transition metal-based catalysts such as nickel and tin are considered as potential catalysts for DEFC due to their oxophilic properties that can improve catalytic activity. In this study, the effect of saccharin on SnNi bimetallic alloy catalyst synthesized by electrodeposition method on copper wire substrate was investigated. SnNi samples were characterized by several techniques, including X-ray diffraction, Scanning electron microscopy, and energi dispersive X-ray spectrocopy. Saccharin addition had a significant effect on the morphology, crystallite size, and composition of the catalyst. The presence of saccharin causes the formation of more uniform particles and has a smaller size. The sample with the addition of saccharin had a smaller charge transfer resistance value 4.82 Ω, lower tafel slope by 115 mV/dec, and show higher jf/jb ratio by 0.55. Furthermore, as the current density decreases, the SnNi catalyst with saccharin has a slow decrease rate and higher stability than the SnNi catalyst without saccharin.